2001
DOI: 10.1007/s00423-001-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical stress reduces mortality from endotoxin shock

Abstract: Surgical stress reduces LPS-induced lethality through biphasically regulating the levels of TNF-alpha and IL-6 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This massive induction, apparently caused primarily by CLP, was significantly inhibited by the 24-h pre-HS ischemic conditioning of the organ. Similarly, in a mild surgical stress and endotoxin double-hit model, Kamei et al (46) found a significant reduction in mortality in the animals receiving both insults days apart with a corresponding inhibition in the endotoxin-induced increase in serum TNF-α and IL-6 levels.…”
Section: Discussionmentioning
confidence: 89%
“…This massive induction, apparently caused primarily by CLP, was significantly inhibited by the 24-h pre-HS ischemic conditioning of the organ. Similarly, in a mild surgical stress and endotoxin double-hit model, Kamei et al (46) found a significant reduction in mortality in the animals receiving both insults days apart with a corresponding inhibition in the endotoxin-induced increase in serum TNF-α and IL-6 levels.…”
Section: Discussionmentioning
confidence: 89%
“…Using both variables provides a more accurate view of postoperative stress. Various cytokines have been used to quantify postoperative stress in both human and animal models [26,27], however, monitoring of these molecular markers have not been routinely used in clinical settings. The observations made in our current study can provide a basis to justify a more precise measurement of postoperative stress, including various inflammatory markers, in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…After opening the abdominal cavity with an incision of 1 cm length, the incision was closed by double layer suture (Vicryl 5.0; Fa Ethicon, Norderstedt, Germany). To prevent metabolic lapse postsurgery mice were provided with 5% glucose solution (Kamei et al., 2002). Additionally the mice were allowed glucose 5% ad libitum (The mean amount received was 6.55 ml/day per mouse in the saline group, and 6.85 ml/day per mouse in the ethanol group).…”
Section: Methodsmentioning
confidence: 99%